Proteomic Analysis Reveals the Phenotypic Heterogeneity and Tolerance Mechanisms of Halophilic Vibrio parahaemolyticus Under Dual Stress of Low Salinity and Bile Salts in the Human Intestine - Yingying Guo; Bing Yang; Xiaoyan Zhou; Zhangxi Gong; Enxiao Wang; Yingjie Pan; Yong Zhao; Haiquan Liu (Biomolecules)
Vibrio parahaemolyticus, a halophilic Gram-negative bacterium commonly found in aquatic products, can colonize the human small intestine, causing gastroenteritis and potentially leukemia. As a major intestinal pathogen, it poses a significant threat to public health. This study aims to investigate the phenotypic heterogeneity of V. parahaemolyticus in the low-salinity and bile salt environments of the human intestinal tract and to elucidate its mechanisms of tolerance and pathogenicity using proteomics. The experimental results indicated that under the low salinity and bile salts conditions of the human intestinal environment, the growth, motility, and biofilm formation of the strains were significantly inhibited. Proteomics analysis revealed that, under these conditions, the energy metabolism, chemotaxis system, flagellar motor, and ribosome-related proteins of V. parahaemolyticus were significantly affected, thereby influencing its growth, motility, and biofilm formation. Furthermore, the activation of the secretion system, particularly the T2SS, enhanced the virulence of secreted factors on host cells. Additionally, the activation of the β-lactam resistance pathway increased resistance to the intestinal environment, thereby enhancing the pathogenicity of V. parahaemolyticus.